Ontogenetic and morphological studies on Tetranychus canadensis (Acari: Tetranychidae) - Liu, Man; Yi, Tian-Ci; Gulbronson, Connor; Bauchan, Gary R.; Ochoa, Ronald (Zootaxa, 2020)
Tetranychus canadensis (McGregor) is redescribed based on type specimens and American non-type specimens. The ontogenetic development of leg chaetotaxy is provided, which is the typical additional pattern for Tetranychus. The variation of pregenital striae and shape of aedeagi are discussed.  Low temperature scanning electron microscopic photos show the supracoxal setae on palpfemur (ep) and leg coxae I (el) are eupathidia; lateral and ventral lips bear modified leaf-like adoral setae (or2 and or3) and the dorsal lips bearing a pair of spine-like dorsal adoral setae (or1); dorsal seta on tibia I (db) is a trichobothrium with a cup-shaped base and broken striae on the inner integument. Confocal scanning shows a thin, long ejaculatory duct and a thicker duct connecting the aedeagus to a cup-shaped seminal vesicle; the aedeagus is hollow where the ejaculatory duct passes through.